Three‐year follow up of using combination therapy with fresh‐frozen plasma and iron chelation in a patient with acaeruloplasminemia. Issue 1 (26th October 2020) - Tridimas, Andreas; Gillett, Godfrey T.; Pollard, Sally; Sadasivam, Nandini; Williams, Adrian; Mellor, Kirsty; Catchpole, Anthony; Stepien, Karolina M.
Abstract: Acaeruloplasminemia is a rare autosomal recessive condition caused by inactivating mutations of the CP gene encoding caeruloplasmin (ferroxidase). Caeruloplasmin is a copper‐containing plasma ferroxidase enzyme with a key role in facilitating cellular iron efflux. We describe a case of a patient with acaeruloplasminemia, confirmed by genetic analysis, treated with combination therapy of monthly fresh‐frozen plasma (FFP) or Octaplas and iron chelation over a 3‐year period. This 19‐year‐old male was diagnosed at the age of 14 after developing issues with social interaction at school prompting investigation. Prior to this, he had been well with a normal childhood. He was found to have an iron deficient picture with a paradoxically high ferritin, with low serum copper and undetectable caeruloplasmin. Genetic testing identified a homozygous splicing mutation, c.(1713 + delG);(c.1713 + delG), in intron 9 of the caeruloplasmin gene. Ferriscan showed a high liver iron concentration of 5.3 mg/g dry tissue (0.17‐1.8). Brain and cardiac T2‐weighted magnetic resonance (MR) imaging did not detect iron deposition of the brain or heart respectively. Treatment with monthly Octaplas infusion was commenced alongside deferasirox (540 mg o.d.) in an attempt to increase caeruloplasmin levels and reduce iron overload, respectively. After 3 years of treatment, there was biochemical improvement with a reduction in ferritin from 1084 (12‐250) to 457 μg/L, ALT from 87 (<50) to 34 U/L together with improvement in his microcytic anaemia. No significant adverse events occurred. This case report adds further evidence of treatment efficacy and safety of combined FFP and iron chelation therapy in acaeruloplasminemia.